Assessing Attitudes toward Nicotine Replacement Therapy for Adolescent Smoking Cessation - Jessica L. King; Tzu-Jung Wong; Julie W. Merten; Jamie L. Pomeranz (University of North Florida, 2016)
The objective was to ascertain attitudes toward nicotine replacement therapy for adolescent tobacco cessation. The authors created a 17-item survey consisting of demographics, quantitative, and qualitative items which was distributed to middle and high school students in North Central Florida. The authors assessed associations and conducted discriminant analyses to compare results by age. One-hundred ninety-eight students completed the survey (57.6% female, 61.6% white). When asked to select the best way to help teens stop using tobacco, combination of methods was most frequently selected (31.6%), followed by "Cold Turkey" (19.5%), e-cigarettes (16.8%), NRT (14.7%), Counseling (10.5%), and Alternative Therapies (6.8%). Qualitative data from students revealed misconceptions toward tobacco use, but an overall awareness that tobacco is a harmful. High school students were more likely than middle school students to agree that nicotine is harmful and e-cigarettes or chewing tobacco are less harmful than traditional cigarettes. Discriminant analyses were inconclusive. These data highlight misconceptions regarding tobacco use and nicotine that might play a role in attitudes toward NRT for adolescent tobacco cessation. Whereas high school students might be more likely to agree nicotine is harmful, their decreased perception of harm of alternative tobacco products such as e-cigarettes or chewing tobacco could be problematic. Further research in this area remains a priority.